The KDM3A–KLF2–IRF4 axis maintains myeloma cell survival - Hiroto Ohguchi (Nature Portfolio, 2016)
Several histone modifiers have been implicated in the survival of multiple myeloma cells. Here, the authors reveal a role for the histone demethylase KDM3A in the survival of this haematologic cancer, and show that mechanistically KDM3A removes H3K9 methylation from the promoters of KLF2 and IRF4, genes essential for myeloma cell survival.